Please Follow through my step-by-step tutorial till the end:
1.) First, move the number(s) to the other side. (algebra rules)
2(x-3)²-32+32=0+32
2(x-3)² = 32
2.) Next, divide every term by 2 to factor out the 2.
2(x-3)²/2 = 32/2
(x-3)² = 16
3.) Third, square root both sides (algebraic rules)
4.) Since the square root of 16 is both +4 and -4, we will have two answers. Next we split the equation in two forms.
(x-3) = 4 (x-3) = -4
x-3+3 = 4+3 x-3+3 = -4+3
x=7 x=-1
5.) So we get two answers x= 7 and x= -1